Effect of screening by clinical breast examination on breast cancer incidence and mortality after 20 years: prospective, cluster randomised controlled trial in Mumbai. (24th February 2021) - Mittra, Indraneel; Mishra, Gauravi A; Dikshit, Rajesh P; Gupta, Subhadra; Kulkarni, Vasundhara Y; Shaikh, Heena Kauser A; Shastri, Surendra S; Hawaldar, Rohini; Gupta, Sudeep; Pramesh, C S; Badwe, Rajendra A
Abstract: Objective: To test the efficacy of screening by clinical breast examination in downstaging breast cancer at diagnosis and in reducing mortality from the disease, when compared with no screening. Design: Prospective, cluster randomised controlled trial. Setting: 20 geographically distinct clusters located in Mumbai, India, randomly allocated to 10 screening and 10 control clusters; total trial duration was 20 years (recruitment began in May 1998; database locked in March 2019 for analysis). Participants: 151 538 women aged 35-64 with no history of breast cancer. Interventions: Women in the screening arm (n=75 360) received four screening rounds of clinical breast examination (conducted by trained female primary health workers) and cancer awareness every two years, followed by five rounds of active surveillance every two years. Women in the control arm (n=76 178) received one round of cancer awareness followed by eight rounds of active surveillance every two years. Main outcome measures: Downstaging of breast cancer at diagnosis and reduction in mortality from breast cancer. Results: Breast cancer was detected at an earlier age in the screening group than in the control group (age 55.18 (standard deviation 9.10) v 56.50 (9.10); P=0.01), with a significant reduction in the proportion of women with stage III or IV disease (37% (n=220) v 47% (n=271), P=0.001). A non-significant 15% reduction in breast cancer mortality was observed in the screening arm versus control arm in the overall study population (age 35-64; 20.82 deaths per 100 000 person years (95% confidence interval 18.25 to 23.97) v 24.62 (21.71 to 28.04); rate ratio 0.85 (95% confidence interval 0.71 to 1.01); P=0.07). However, a post hoc subset analysis showed nearly 30% relative reduction in breast cancer mortality in women aged 50 and older (24.62 (20.62 to 29.76) v 34.68 (27.54 to 44.37); 0.71 (0.54 to 0.94); P=0.02), but no significant reduction in women younger than 50 (19.53 (17.24 to 22.29) v 21.03 (18.97 to 23.44); 0.93 (0.79 to 1.09); P=0.37). A 5% reduction in all cause mortality was seen in the screening arm versus the control arm, but it was not statistically significant (rate ratio 0.95 (95% confidence interval 0.81 to 1.10); P=0.49). Conclusions: These results indicate that clinical breast examination conducted every two years by primary health workers significantly downstaged breast cancer at diagnosis and led to a non-significant 15% reduction in breast cancer mortality overall (but a significant reduction of nearly 30%in mortality in women aged ≥50). No significant reduction in mortality was seen in women younger than 50 years. Clinical breast examination should be considered for breast cancer screening in low and middle income countries. Trial registration: Clinical Trials Registry of India CTRI/2010/091/001205; ClinicalTrials.gov NCT00632047 .